Leveraging AFCFTA for Regional Supply Chain Integration and Competitiveness (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The African Continental Free Trade Area (AfCFTA) represents the most ambitious integration project in Africa’s contemporary economic history, carrying the potential to reshape regional supply chains and reposition the continent within global trade dynamics. Yet the extent to which the agreement can deliver meaningful competitiveness hinges on how effectively African economies leverage its provisions to deepen productive linkages, harmonise regulatory frameworks, and stimulate cross-border industrial cooperation. This study examines the strategic pathways through which AfCFTA can serve as a catalyst for supply chain integration across the continent, with particular attention to the institutional, infrastructural, and policy foundations required for its success. Drawing on comparative experiences from established regional blocs including the European Union, ASEAN, and the USMCA, the research highlights global lessons that can inform Africa’s own integration trajectory. The paper also interrogates the current structure of intra-African trade, identifying persistent fragmentation, limited manufacturing depth, and infrastructural deficits as major impediments to cohesive regional value chains. Within this context, the AfCFTA’s core protocols on trade in goods, services, investment, and digital commerce are analysed as critical tools capable of reducing transaction costs, creating market predictability, and fostering cross-border production networks. The study further evaluates the enabling role of trade facilitation, logistics optimisation, digital transformation, and sustainable financing in building resilient supply chains that can withstand global shocks. The paper argues that realising the competitiveness promise of AfCFTA requires coordinated policy alignment, targeted investments in regional infrastructure, and a deliberate shift towards technology-driven industrialisation. By outlining concrete strategic priorities, the study contributes to ongoing debates on Africa’s integration agenda and offers actionable insights for governments, private sector actors, and development institutions committed to strengthening the continent’s position in global value chains.